Heritable Effect of Plant Water Availability Conditions on Restoration of Male Fertility in the “9E” CMS-Inducing Cytoplasm of Sorghum - Elkonin, Lev A.; Tsvetova, Marina I. (Frontiers in Plant Science, 2012)
Heritable changes of phenotype arising in plant ontogenesis by the influence of environmental factors belong to the most intriguing genetic phenomena. Studying restoration of male fertility in the ‘9E’ type of CMS-inducing cytoplasm of sorghum and related CMS-inducing cytoplasms, A4 and M35-1A, in some hybrid combinations, we found an unusual inheritance pattern: the Rf-genes functioned in the self-pollinated progenies of F1 hybrids (up to F10) but did not or poorly expressed in backcrosses of these hybrids to CMS-lines with the same cytoplasm type. In experiments on parallel growing of the same F1 hybrid combinations in the ‘dry plot’ and in the ‘irrigated plot’, it was found that high level of plant water availability during panicle and pollen developmental stages significantly increased male fertility of F1 and testcross hybrid populations, in which fertility-restoring genes were in heterozygote state, whereas in F2 populations the influences of water availability conditions cause less pronounce effects. Similarly, male-sterile F1 plants, being transferred from the ‘dry plot’ to greenhouse, produced male-fertile panicles. In addition, male-sterile plants from F2 families, which segregated-out as recessives, being transferred to greenhouse also produced male-fertile panicles. In the progenies of these revertants that were grown in field conditions and in the ‘dry plot’, stable inheritance of male fertility for 3 cycles of self-pollination was observed, and a number of stable fertile lines in the ‘9E’ cytoplasm were obtained. However, in test-crosses of these fertile lines to CMS-lines with the ‘9E’ cytoplasm restoration of male fertility was not observed, except the progeny of one revertant that behaved as fertility-restorer line. These data suggest that the functional state of fertility-restoring genes for the ‘9E’ sorghum cytoplasm is epigenetically-regulated trait established by the influence of environmental factors and is transmitted to sexual generations.